PRODUK KULIT DECRAFTSMAN DALAM FOTOGRAFI KOMERSIAL - Dodi Wahyu Pranoto; Muhammad Fajar Apriyanto; Oscar Samaratungga (Specta: Journal of Photography, Arts, and Media, 2021)
Decraftsman Leather Product in Commercial Photography. Commercial photography is a genre of photography that aims to promote a product or service. This genre of photography can be- come means of promotion especially those unknown to the public, like Decrafstman products. Craft industry Decrafstman is in Trenggalek District, East Java produces various genuine leather based products. However, it is unfortunate that the Decraftsman production house does not have a visual form of a photo that is adequate for promotional purposes or to attract people to work together. The creation of this work aims to help Decraftsman advertise their local brand products with interest- ing visual by creating stil life photography works using the Decraftsman’s production room as the background for the creation. The methods employed were observation and exploration, while in the experiment stage, the focus was more on the stages of photographing the products. The results of this creation can be used as a medium for promotion through social media such as Instagram so that the public is more familiar with Decraftsman products. ABSTRAKFotografi komersial merupakan salah satu jenis fotografi yang bertujuan untuk mempromosikan suatu produk atau jasa. Saat ini masih banyak masyarakat yang belum mengetahui keuntungan pembuatan produk berbahan dasar kulit asli. Kulit adalah lapisan luar tubuh binatang yang merupakan suatu kerangka luar, tempat bulu binatang tumbuh. Produk Decraftsman memiliki kelebihan yaitu dapat memproduksi berbagai macam produk berbahan dasar kulit asli. Namun sangat disayangkan rumah produksi Decraftsman tidak memiliki bentuk visual sebuah foto yang memadai untuk tujuan promosi maupun menjadi daya tarik masyarakat untuk bekerja sama. Penciptaan karya ini menampilkan produk Decraftsman yang dikemas dalam sebuah karya fotografi stil life dengan menggunakan ruang produksi dari Decraftsman sebagai latar belakang pembuatan. Selain itu dalam proses pembuatan karya juga menggunakan elemen pendukung yang berupa alat produksi kulit. Hasil dari penciptaan ini dapat digunakan sebagai media untuk promosi melalui media sosial seperti Instagram agar masyarakat lebih mengenal produk Decraftsman